Perlindungan Desain Industri dalam Upaya Memajukan Produk Lokal dalam Era Revolusi Industri 4.0 - M. Faisal Rahendra Lubis; Masnun Masnun (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2020)
The potential for intellectual property in terms of industrial design is vast, especially in supporting the national economy. Therefore, legal protection for industrial design urgently needs, which will have an impact on the emergence of much creativity from creators in creating new designs, especially in the era of the industrial revolution 4.0. Recognition of the protection of intellectual property rights is philosophically closely related to the school of thought or natural law doctrine which emphasizes the human factor in using his mind to solve problems faced in all aspects of his life. Law Number 31 of 2000 concerning Industrial Design enacted to provide opportunities for designers who came from the Small and Medium Enterprises group that controlled nearly 90% of businesses in the State of Indonesia, which expected to take advantage of the protection of these Industrial Designs.